2008
DOI: 10.1007/s00436-008-0965-9
|View full text |Cite
|
Sign up to set email alerts
|

Field study on the efficacy of an extract of neem seed (Mite -Stop®) against the red mite Dermanyssus gallinae naturally infecting poultry in Egypt

Abstract: Infestations with the poultry red mite Dermanyssus gallinae represent a major ectoparasite problem in poultry and affects egg and meat production worldwide. The effects of the neem seed product Mite-Stop against the red poultry mite were investigated. Five primitive poultry farms in two small villages in the Nile Delta and Giza district were selected for the study. The neem extract was diluted 1:40 and 1:50 with tap water just prior to use. Application of the two dilutions of the provided product was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 15 publications
1
17
1
1
Order By: Relevance
“…However, the second treatment increased the dramatic reduction of the mite population. [41] The mite mortality in the present study was not as good as the one reported in the above research. The difference may be due to the species and methods of administration.…”
Section: Resultscontrasting
confidence: 78%
“…However, the second treatment increased the dramatic reduction of the mite population. [41] The mite mortality in the present study was not as good as the one reported in the above research. The difference may be due to the species and methods of administration.…”
Section: Resultscontrasting
confidence: 78%
“…However, many of them can only be used with several precautions, since they may harm health of humans and animals or may produce residuals inside the body of farm animals, respectively, inside eggs (Mehlhorn 2008). Therefore, in recent times, many plant extracts have been tested, whether they work against endo-or ectoparasites and/or against pests, which may contaminate food and/or rooms with agents of diseases (Schmutterer 2002;Athanasiadou et al 2007;Bäumler 2007;Brown 1996;Fajimi and Taiwo 2005;Leung 1985;Mehlhorn et al 2005, Mehlhorn 2008Mehlhorn et al 2005Mehlhorn et al , 2006Mehlhorn et al , 2010Michaelakis et al 2009;Oladimeji et al 2000;Amer and Mehlhorn 2006;Abdel-Ghaffar and Semmler 2007;Abdel-Ghaffar et al 2008a, b, 2009Heukelbach et al 2006;Kim et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Other workers (Omar et al 2003) have demonstrated that purified extracts of Azadirachta indica and other members of the Meliaceae family containing gedunin showed significant in vitro, but poor in vivo, antimalarial activity. Patented di-basic-ester extracts of A. indica have been proven in several in vivo and in vitro tests to eliminate infestations with head lice, P. humanus capitis (Heukelbach et al 2006;Abdel-Ghaffar and Semmler 2007); scabies mites, Sarcoptes scabiei (Abdel-Ghaffar et al 2008b); or red chicken mites, Dermanyssus gallinae (Abdel-Ghaffar et al 2008a. Seed extracts of A. indica, Vitex agnus castus and Eucalyptus citriodora oil were tested on repellent effects against mosquitoes, Aedes aegypti, Culex quinquefasciatus, ticks, Ixodes ricinus, Dermacentor reticulates, Rhipicephalus sanguineus, head lice, P. humanus capitis, and mites, Dermanyssus gallinae ).…”
Section: Introductionmentioning
confidence: 99%